?PETROGENESIS OF HAZARA DOLOMITES OF NWFP, PAKISTAN AND THEIR INDUSTRIAL USES (Biological Sciences - PJSIR, 1997)
Hazara dolomites are sedimentary rocks of Cambrian age and belong to Sirban formation of Abbottabad Group. These dolorni tcs are formed by the alteration of limestones. There are huge resources ofdolomite in the Sirban formation ofAbbottabad area. Two textural varieties are found inthese dolomites, one iscoarsc grained and the other is fine grained. Chemical analysis shows that thesc dolomites have many industrial applications. These are suitable for using as soil neutralizer, in the preparation of dolomite clinker, as an accelerator in the cement industry, in the preparation of chemicals like MgO, Mg(OH)2 and in the steel industry.